Dental services provided by dentists in Australia. (23rd December 2019) - Brennan, DS; Chrisopoulos, S; Luzzi, L; Teusner, DN
Abstract: Objectives: To examine the efect of age and gender on dental services provided by dentists in Australia, and compare with previous estimates across the period 1983–1984 to 2013–2014. Methods: Data were collected by mailed survey from a random sample of Australian dentists. Private sector dentists were the focus of the analysis. Data were weighted to the age and sex distribution of Australian practising dentists. Results: The analysis was based on service logs collected from n = 211 dentists. Adjusted results (rate ratio, 95% CI) showed male dentists had higher endodontic rates (1.7, 1.0–2.9) than female dentists. Dentists aged 40–49 years had higher restorative rates (1.6, 1.1–2.2) but lower preventive rates (0.5, 0.3–0.9) than those aged 20–29 years. Diagnostic services were lower for dentists aged 40–49 to 60+ years (0.8, 0.6–0.9), while denture services were higher for dentists aged 40–49 (11.1, 2.5–48.5) to 60+ years (6.4, 1.2–33.3). Crowns were higher for dentists aged 40–49 (2.4, 1.0–5.6) and 50–59 years (2.9, 1.3–6.6). Diagnostic and preventive services were consistently higher across 1983–1984 to 2013–2014. Conclusions: Younger dentists provided higher rates of diagnostic and preventive services. Over a 30‐year period, there was a consistent trend towards higher provision of diagnostic and preventive services.